Detection of Diazinon Residue in Honey and Honey Bee (Apis mellifera) in Bandar-Abbas and Meshkinshahr, Iran - Fatemeh Bagheri; Hassan Vatandoost; Mansoureh Shayeghi; Yavar Rassi; Ahmad Ali Hanafi-Bojd; Abbas Rahimi-Foroushani; Alireza Razavi; Fatemeh Nikpour Alkaran (Tehran University of Medical Sciences, 2018)
Background: The excessive use of pesticides for crops by farmers, their destructive effects on beneficial organisms, such as bees, have become a big problem today. This study was designed to find out if the honey bee (Apis mellifera) and the honey be affected by diazinon. Methods: Six hives were purchased, 3 hives in Bandar-Abbas and remaining were considered for Meshkinshahr. Plants around the hive were sprayed with diazinon at a concentration of 2/1000. Sampling took place 15d after spraying, and diazinon residue was measured by the HP TLC. The study was conducted in 2017-2018. Results: The amount of diazinon residue in honey and honey bee was measured and compared with existing studies. The amount of diazinon residue in honey bee was found to be 0.017mg/kg in Bandar Abbas, and 0.005mg/kg in Meshkinshahr hives. There was nothing in honey. Conclusion: Honey is safe for consumers.